1987
DOI: 10.1002/syn.890010408
|View full text |Cite
|
Sign up to set email alerts
|

Review: D1 dopamine receptor—the search for a function: A critical evaluation of the D1/D2 dopamine receptor classification and its functional implications

Abstract: The present review focuses on the hypothesized D1/D2 dopamine (DA) receptor classification, originally based on the form of receptor coupling to adenylate cyclase activity. The pharmacological effects of compounds exhibiting putative selective agonist or antagonist profiles at those DA receptors positively coupled to adenylate cyclase activity (D1 DA receptors) are extensively reviewed. Comparisons are made with the effects of putative selective D2 DA receptor agonists and antagonists, and on the basis of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
227
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(237 citation statements)
references
References 351 publications
(428 reference statements)
10
227
0
Order By: Relevance
“…Although apparently puzzling, this D 1 /D 2 antagonist/antagonist interaction has been reported previously (for a review see Clark and White 1987). Indeed, SCH23390, ineffective alone, prevented the facilitation of striatal ACh (Saller and Salama 1986) and GABA (Harsing and Zigmond 1997) Effect of raclopride and SCH23390 on the NMDA-stimulated glutamate (GLU) release.…”
Section: Discussionmentioning
confidence: 82%
“…Although apparently puzzling, this D 1 /D 2 antagonist/antagonist interaction has been reported previously (for a review see Clark and White 1987). Indeed, SCH23390, ineffective alone, prevented the facilitation of striatal ACh (Saller and Salama 1986) and GABA (Harsing and Zigmond 1997) Effect of raclopride and SCH23390 on the NMDA-stimulated glutamate (GLU) release.…”
Section: Discussionmentioning
confidence: 82%
“…A study in rats using dopamine D 2 receptor antagonists showed that lower dopamine D 2 receptor availability does not alter cocaine self-administration (Caine and Koob 1994). However, the difference in recovery times for dopamine D 1 receptor binding versus dopamine D 2 receptor binding may lead to abnormalities in the putative opposing andրor synergistic relationships between dopamine D 1 and D 2 receptor subtypes (Clark and White 1987;Self et al 1996;Wang and McGinty 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Microdialysis studies have shown that 22 hours following the last administration of chronic binge cocaine, baseline dopamine levels are significantly decreased, whereas cocaine continues to cause immediate elevations in striatal dopamine levels after each injection (Maisonneuve and Kreek 1994;Maisonneuve et al 1995). Increased activation of dopamine receptors by the increased concentrations of dopamine during cocaine administration may mediate many of cocaine's reinforcing effects (Ritz et al 1987;Clark and White 1987).…”
mentioning
confidence: 99%
“…With the advant of the D1 selective ligands, D1-like receptors are distinguished from the D2-like receptors [1][2][3] . Then D1-like receptor subtypes, D1 receptor (D1R) and D5 receptor (D5R), are further identified in mammalian brain by cDNA cloning [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%